The use of military planning techniques to manage outbreaks of novel infections in acute inpatient settings: development of an 'infection control estimate' (ICE). Issue 2 (March 2021) - Wynn, Matthew Oliver; George, Ryan; Cole, Mark
Outbreaks of infection create unique challenges to healthcare leaders and members of infection control teams who lead efforts to manage, control and resolve outbreaks. This is especially true during outbreaks of novel pathogens which may require atypical control methods reflecting the unknowns inherent in such situations. Healthcare providers within the UK have adopted various structures and models of infection prevention and control (IPC) service reflecting the individual needs of different organisations. As such, the roles and responsibilities of IPC practitioners vary between organisations. Variations in models of care combined with challenges created by outbreaks of novel infections may make algorithm based approaches to outbreak management less effective and potentially prone to missing key actions or considerations which may improve outcomes. Here we suggest the application of a widely established military planning technique, developed to aid decision making in combat environments, to the management of outbreaks of novel infection in acute hospital settings. The technique can be applied at all levels within an IPC hierarchy regardless of role or responsibility and may improve the coherency and efficacy of outbreak management efforts made by IPC teams. The technique may also be applied to outbreaks of known infections; however, in order to demonstrate the flexibility of the model, a novel infection has been used to illustrate its potential value in outbreak management when knowledge is limited.